Unified methodology for strength and stress analysis of structural concrete members - Oukaili, Nazar (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a methodology is presented for determining the stress and strain in structural concrete sections, also, for estimating the ultimate combination of axial forces and bending moments that produce failure.
Keywords: curvature; secant modulus; uniaxial stress-strain; extinction of prestressing; cracking; deformability